The Correlation Between Family History, Constipation, Defecation Position, And Defecation Time And Hemorrhoid On Patient In General Surgery Outpatient Clinic Dr. Mohamad Soewandhie Regional Public Hospital Surabaya - Tevin, Lovita Roderica; Arifin, Fransiscus; Pramono, Adi (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
Background: Hemorrhoid is one of the most common anorectal problem. Definite etiological cause(s) are still unknown but there are many risk factors that are found to be responsible for the development of hemorrhoid. Elimination and modification of these risk factors are the keys toward the effective control and prevention of hemorrhoid. Aim: This study aims to analyze the correlation between family history, constipation, defecation position, and defecation time and hemorrhoid among patient in general surgery outpatient clinic Dr. Mohamad Soewandhie Regional Public Hospital Surabaya. Methods: This was an analytic observational study with cross-sectional design. Sampling was conducted with purposive sampling technique. Coefficient contingency test was done to analyze correlation between bivariate variables. Fifty-six patients in June and July 2016 were given questionnaire and patient’s medical records were taken to know the presence of hemorrhoid. Results: There was a correlation, respectively, between family history and hemorrhoid (C=0,329; p=0,009), constipation and hemorrhoid (C=0,474; p=0,000), between defecation position and hemorrhoid (C=0,395; p=0,001), and between defecation time and hemorrhoid (C=0,448; p=0,000). Conclusion: The incidence of hemorrhoid could be affected by family history, constipation, defecation position, and defecation time.